Pemetaan Tren Global pada Bahaya Academic Burnout di Lingkungan Akademik: Sebuah Kajian Bilbliometrik: - Muhammad Fikri Fauzi; Nadia Amalia (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2026)
Academic burnout that is not addressed seriously has the potential to cause dangerous impacts such as despair, feelings of anxiety, decreased enthusiasm for life, and can even lead to thoughts of suicide. This study analyzes global trends in the dangers of academic burnout using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, with the Dimensions AI source database accessed on February 12, 2026, and the keyword 'Academic Burnout' over the past ten years. Initial results showed a total of 340,247 works, of which only 733 remained that fit the research category. In general, the global trend of publication of related articles experienced an exponential increase, except in 2019 and 2023, during the early and late periods of the COVID-19 pandemic. The global citation trend shows a curve that continues to rise exponentially, with no decline. VOS Viewer visualization also complements the results of this study, including network, overlay, and density visualizations, along with their explanations. Data on active researchers and journals is also presented in this study. Heta Tuominen from the University of Eastern Finland, Finland, and Frontiers in Psychology are active researchers and journals on this topic. The results of this study are expected to broaden understanding of academic burnout and serve as a foundation for educational policy development, particularly in this context.